PROSEDUR PEMERIKSAAN RADIOGRAFI COLON IN LOOP PADA PEDIATRIK DENGAN KASUS HIRSCHSPRUNG DISEASE DI INSTALASI RADIOLOGI RS MUHAMMADIYAH LAMONGAN - Rumaf, As`syifa Distia; Mukmin, Amril; Liscyaningsih, Ike Ade Nur (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Hirschsprung Disease is a functional obstruction of the colon characterized by the absence of ganglion cells in the myenteric and submucosal plexuses of the distal segment, resulting in the absence of peristaltic movement. One of the radiographic methods used to assess this condition is the colon in loop examination, a technique involving retrograde administration of positive or negative contrast media into the colon. This study aims to describe the radiographic procedure of colon in loop in pediatric patients with suspected Hirschsprung Disease and to determine the reasons for not performing a post-evacuation radiograph at the Radiology Department of Muhammadiyah Hospital Lamongan. This research employed a qualitative case study approach, with data collected in July 2025 through observation, interviews, and documentation. The research subjects consisted of one radiologist and three radiographers. The findings indicate that the procedure was performed without specific preparations, except for changing the patient’s clothing to examination attire. The examination began with a plain abdominal radiograph in the AP projection, followed by contrast images in the Lateral, AP, LPO, and RPO projections using a water-soluble contrast medium with a single-contrast technique at a 1:8 ratio, totaling 200 cc. The contrast was introduced slowly through a catheter inserted approximately 2.5 cm into the anus and secured with a balloon filled with sterile water. A post-evacuation radiograph was not performed because the contrast medium used is easily absorbed by the body. In conclusion, the colon in loop procedure at the Radiology Department of Muhammadiyah Hospital Lamongan is carried out in a straightforward manner with specific projection sequences, the use of water-soluble contrast suitable for pediatric patients, and without the need for a post-evacuation radiograph due to the rapid absorption characteristics of the contrast medium. ABSTRAKHirschsprung Disease adalah gangguan fungsi kolon yang ditandai dengan tidak adanya sel ganglion pada pleksus mienterikus dan submukosa di segmen distal, sehingga pergerakan peristaltik tidak terjadi dan menimbulkan obstruksi fungsional. Salah satu metode radiografi yang digunakan untuk mengevaluasi kondisi tersebut adalah pemeriksaan colon in loop, yakni teknik pengisian kolon menggunakan media kontras positif atau negatif secara retrograd. Penelitian ini bertujuan mendeskripsikan prosedur pemeriksaan radiografi colon in loop pada pasien pediatrik dengan dugaan Hirschsprung Disease serta mengidentifikasi alasan tidak dilaksanakannya foto post-evakuasi di Instalasi Radiologi RS Muhammadiyah Lamongan. Penelitian menggunakan pendekatan kualitatif melalui studi kasus, dengan pengumpulan data pada Juli 2025 melalui observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri atas seorang dokter spesialis radiologi dan tiga radiografer. Hasil penelitian menunjukkan bahwa pemeriksaan dilakukan tanpa persiapan khusus, kecuali penggantian pakaian pasien. Pemeriksaan diawali dengan foto polos abdomen proyeksi AP, dilanjutkan dengan proyeksi kontras Lateral, AP, LPO, dan RPO menggunakan media kontras water soluble teknik single contrast dengan perbandingan 1:8 sebanyak 200 cc. Kontras dimasukkan perlahan melalui kateter yang dimasukkan sekitar 2,5 cm ke anus dan distabilkan menggunakan balon berisi aquabidest. Foto post-evakuasi tidak dilakukan karena jenis kontras yang digunakan mudah diserap tubuh. Penelitian ini menyimpulkan bahwa prosedur colon in loop di rumah sakit tersebut dilakukan secara sederhana dengan urutan proyeksi tertentu, pemilihan media kontras yang aman bagi pasien pediatrik, serta tanpa perlunya foto post-evakuasi akibat sifat kontras yang cepat terabsorpsi.